2016
DOI: 10.1007/s00432-015-2111-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor characteristics and therapy of elderly patients with breast cancer

Abstract: The older group's reduced disease-free survival could be explained by the tumor characteristics and differences in the adjuvant treatment. Remarkably, elderly women are more likely to be overtreated surgically while being undertreated in terms of adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
6
15
0
Order By: Relevance
“…Radiotherapy after primary surgery was performed less frequently in the oldest age group in a study by Weggelaar et al [37] agreeing with our results and with previous studies reporting less loco-regional surgery and frequent omission of radiotherapy in elderly patients [34, 36, 3941]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Radiotherapy after primary surgery was performed less frequently in the oldest age group in a study by Weggelaar et al [37] agreeing with our results and with previous studies reporting less loco-regional surgery and frequent omission of radiotherapy in elderly patients [34, 36, 3941]. …”
Section: Discussionsupporting
confidence: 93%
“…A subgroup analysis from the herceptin adjuvant study (HERA) showed an effect of trastuzumab independent of age [33]. In line with the findings of Grumpelt et al, we observed that the use of trastuzumab was insufficient both in the ESG and the NESG [34]. …”
Section: Discussionsupporting
confidence: 84%
“…The causes of lower rates of improvement in the survival of elderly and widowed patients with localized disease and of Caucasians with ER-and PRdisease compared with those observed in younger patients and patients with ER+ and PR+ disease, respectively, may be multivariate. Standard guideline therapy, including surgery, are not administered to elderly patients at the same rate as to younger women (47)(48)(49)(50). Co-morbidities in older women often result in faster deterioration following chemotherapy than in younger women and are significant factors in therapeutic decisions and survival (51).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patients in the older group may not have been referred for breast cancer screening at all given the recommended age limit for screening of 70-75 years. The comparable nodal status could suggest a different or more benign pattern of tumor progression in elderly patients [7,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%